Rancang Bangun Sistem Pengelolaan Data dan Pelayanan Jasa pada Berkah Laundry Karangasem Berbasis Website - Wuyo, Panty (Universitas Methodist Indonesia, 2024)
Berkah Laundry is a laundry services in the Karangasem Laweyan at Surakarta. Berkah Laundry has been established for three years. The main focus of services at Berkah Laundry is washing and ironing clothes. Berkah Laundry does not use a computerizedsystem at this time. Managing customer data and report data is still done manually withevery recording activity report in a book. Therefore, the laundry owner experienced problems when checking the previously recorded data. The final project aims to build a website-based data management system and services at Berkah Laundry Karangasem.It is expected to assist in managing customer data and report data. The website was built using the waterfall method. The collecting data method implemented literature study, observation, and interviews. System design used UML system design. The implementation process used PHP and MySQL databases. System display design usedHTML 5 and CSS. This system consists of 2 users, namely customers and admin. Customers have access to login, order laundry services, view laundry information, vieworder lists, and view order notes. Admins have access to login, manage customer data, manage admin data, manage order data, manage receipt data, view the recap of incomedata, and view the recap of data order. The system testing process used the webqual 4.0 method and multiple regression. Based on the test, the results show 0.810 or equalto 81.0%. It shows a value that indicates that the user feels helped by the system.